Some Results on \(r\)-Row-Regular Circulant Partial Hadamard Matrices of Order \((k × 2k)\) - Manjhi, Pankaj Kumar; Rana, Mahendra Kumar (Communications in Mathematics and Applications, 2022)
This paper provides some new results on \(r\)-row-regular circular partial Hadamard matrices of order \((k× 2k)\), and also discusses the possible linear relationship between \(r\) and \(k\). Furthermore, a method of constructing such a matrix is given.
Keywords: Hadamard matrix; Circulant matrix; Partial Hadamard matrix; Orthogonal design